KOMBINASI AROMATERAPI DAN TERAPI MUSIK TERHADAP KECEMASAN REMAJA SELAMA BELAJAR DARING DI ERA PANDEMIC COVID-19 DI SEMARANG - Novita Wulan Sari; Margiyati; Nur Sholiha Rositayani; Samuel Sebastian Tamba (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2022)
Adolescence is a period of transition or transition due to biological and psychological growth, development, and changes. Biological changes are marked by the growth and development of primary sex, while psychological changes are characterized by changes in attitudes, feelings, and emotions. This transitional period is dubbed a period full of storms and stress, because it causes emotional upheaval, anxiety, and discomfort because the teenager is required to adapt and accept all the changes that occur. The role of nurses that can be used is to provide complementary therapies, namely a combination of aromatherapy and music therapy in reducing anxiety during online learning. The method in this study is a quasi-experimental design with a pre-post test with control group. The sampling technique used was purposive sampling with a total of 60 respondents. The treatment was given in 4 sessions for 4 weeks. The treatment given is a combination of aromatherapy and music therapy. The measuring instrument used is the RCMAS anxiety instrument. The results of this study showed the effect of giving a combination of aromatherapy and music therapy on adolescent anxiety levels during online learning during the covid-19 pandemic (p <0.05). The results of the study are recommended to be able to reduce anxiety in adolescents during online learning during the covid-19 period.